2017
DOI: 10.2147/ijn.s128775
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and cytocompatibility of an implant coating consisting of TiO<sub>2</sub>&nbsp;nanotubes combined with a GL13K antimicrobial peptide

Abstract: Prevention of implant-associated infections at an early stage of surgery is highly desirable for the long-term efficacy of implants in dentistry and orthopedics. Infection prophylaxis using conventional antibiotics is becoming less effective due to the development of bacteria resistant to multiple antibiotics. An ideal strategy to conquer bacterial infections is the local delivery of antibacterial agents. Therefore, antimicrobial peptide (AMP) eluting coatings on implant surfaces is a promising alternative. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 43 publications
0
45
0
1
Order By: Relevance
“…Self-organized and vertically oriented titanium oxide nanotubes loaded with the broad spectrum AMP HHC36 showed in vitro bactericidal activity against S. aureus in liquid surrounding the nanotubular surface and reduced bacterial colonization on the surface ~200-fold (Ma et al, 2012 ). GL13K-eluting coatings on these titanium oxide nanotubes prevented growth of Fusobacterium nucleatum and P. gingivalis in an in vitro disk-diffusion assay (Li et al, 2017 ). In vitro release of Tet213 from microporous calcium phosphate coatings applied on titanium showed bactericidal activity against S. aureus and P. aeruginosa (Kazemzadeh-Narbat et al, 2010 ).…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…Self-organized and vertically oriented titanium oxide nanotubes loaded with the broad spectrum AMP HHC36 showed in vitro bactericidal activity against S. aureus in liquid surrounding the nanotubular surface and reduced bacterial colonization on the surface ~200-fold (Ma et al, 2012 ). GL13K-eluting coatings on these titanium oxide nanotubes prevented growth of Fusobacterium nucleatum and P. gingivalis in an in vitro disk-diffusion assay (Li et al, 2017 ). In vitro release of Tet213 from microporous calcium phosphate coatings applied on titanium showed bactericidal activity against S. aureus and P. aeruginosa (Kazemzadeh-Narbat et al, 2010 ).…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…As a result, peptide loaded TiO 2 nanotube surface effectively killed S. aureus in vitro, and the release of the AMP from the nanotubes was verified via liquid chromatography coupled mass spectrometry (LC-MS) analysis [ 134 ]. Furthermore, GL13K peptide loaded in TiO 2 nanotubes, on titanium surfaces, by a simple soaking technique demonstrated a sustained and slow drug release profile in vitro and eradicated the growth of Fusarium nucleatum and P. gingivalis within 5 days of exposure [ 133 ].…”
Section: Surface-immobilized Peptides On Medical Implantsmentioning
confidence: 99%
“…In the second study, TNTs implants were coated with basic fibroblast growth factor (bFGF) in combination with a biodegradable polymer (PLGA) and analyzed by histomorphometry also after 12 weeks . The results of both studies showed a significant increase in bone cell adhesion and proliferation for the groups containing growth factors when compared to the anodized‐only control groups, suggesting a positive influence of the incorporation of growth factors to the TNTs surfaces in terms of the quality and quantity of the observed bone formation …”
Section: Drug Delivery Systemmentioning
confidence: 93%
“…tested in vitro the bacterial cultures on TNTs surfaces with GL13K antimicrobial peptides for their known antibacterial spectrum, using a simple soaking technique. The peptide incorporation did not affect the surface biocompatibility, and the previously cultured Fusobacterium nucleatum and Porphyromonas gingivalis bacterial colonies were eradicated from TNTs surfaces after 5 days of antibiotic activation …”
Section: Drug Delivery Systemmentioning
confidence: 96%